2020
DOI: 10.1002/jcop.22360
|View full text |Cite
|
Sign up to set email alerts
|

Life satisfaction in Chinese rural‐to‐urban migrants: Investigating the roles of self‐esteem and affect balance

Abstract: The goal of the present article is to investigate whether positive and negative affects mediate or moderate the impact of self‐esteem on life satisfaction among Chinese rural‐to‐urban migrants. Participants contained 712 rural‐to‐urban migrants recruited from four construction sites in China, who were evaluated with Rosenberg Self‐Esteem Scale, Positive and Negative Affect Scale, and Satisfaction with Life Scale. Correlation analysis indicated self‐esteem positively predicted life satisfaction. In addition, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 45 publications
2
16
0
Order By: Relevance
“…As a consequence of this, individuals who experience high levels of positive emotions have an ability to produce various possible coping strategies in the face of adversity (Fredrickson, & Joiner, 2002). Consistent with the outcomes of this study, previous research indicated that affect balance was associated with a variety of quality of life and psychological health outcomes, including depressive symptoms, resilience, and self-esteem (Arslan, 2015a;Karaırmak & Siviş-Çetinkaya, 2011;Kelle & Uysal Irak, 2018;Liang et al, 2020;Pieruccini-Faria et al, 2018;Veronese et al, 2018). For example, Arslan (2015b) found a large predictive effect of positive affectivity on resilience, and positive affect was reported as an important source in the building of resilience in adolescence to adulthood (Arslan, 2016;Tugade & Fredrickson, 2004).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…As a consequence of this, individuals who experience high levels of positive emotions have an ability to produce various possible coping strategies in the face of adversity (Fredrickson, & Joiner, 2002). Consistent with the outcomes of this study, previous research indicated that affect balance was associated with a variety of quality of life and psychological health outcomes, including depressive symptoms, resilience, and self-esteem (Arslan, 2015a;Karaırmak & Siviş-Çetinkaya, 2011;Kelle & Uysal Irak, 2018;Liang et al, 2020;Pieruccini-Faria et al, 2018;Veronese et al, 2018). For example, Arslan (2015b) found a large predictive effect of positive affectivity on resilience, and positive affect was reported as an important source in the building of resilience in adolescence to adulthood (Arslan, 2016;Tugade & Fredrickson, 2004).…”
Section: Discussionsupporting
confidence: 77%
“…Resilience was also found to have a direct effect on psychological health (Gloria, & Steinhardt, 2016). Furthermore, research shows that affect balance is associated with a wide range of factors including meaningful living (Ho et al, 2010;Steger et al, 2006;Steger, Oishi, et al, 2009;Yalçın & Malkoç, 2015), health-related quality of life (Moon, Yoon, Jeong, & Cho, 2018), daily emotional experiences (Veilleux et al, 2020), depressive symptoms (Pieruccini-Faria, Muir-Hunter, & Montero-Odasso, 2018), personal well-being and social capital (Veronese, Pepe, Dagdukee, & Yaghi, 2018), and self-esteem (Liang, Xu, Xia, & Ma, 2020). With regards to resilience, growing literature demonstrates that resilience is a significant predictor of meaningful living (Kleiman, & Beaver, 2013), psychological distress, subjective well-being, and quality of life (Tecson, Wilkinson, Smith, & Ko, 2019), affect balance, life satisfaction, and psychosocial well-being, and decreased negative affect (Yildirim, 2019), moods, depression, and anxiety (Burns, Anstey, & Windsor, 2011).…”
Section: Affective Balance Resilience and Psychological Healthmentioning
confidence: 99%
“…Multiple studies have addressed the direct relationship between life satisfaction and self-esteem 3 , 36 , 48–54 but the psychological mechanisms that underlie this association are still unknown. Therefore, the present research has attempted to go beyond the direct link between both constructs by examining the potential mediator of self-presentation.…”
Section: Introductionmentioning
confidence: 99%
“…Total scores of the RSES range from 10 to 40, and higher scores indicate higher level of self-esteem. The Chinese version of the RSES was translated by Ji and exhibited adequate internal consistency in migrants and adolescents (Cronbach’s alpha = 0.81; Liang et al, 2020 ; Wang et al, 2021b ).…”
Section: Methodsmentioning
confidence: 99%